Problems of bioanalytical part of bioequivalence studies of drugs in Russia - A. L. Khokhlov; E. G. Lileeva; O. A. Sinitsyna; S. A. Speshilova; S. M. Demarina; L. N. Shitov (LLC "Publisher OKI", 2014)
In the review of the main problems holding bioanalytical part of bioequivalence studies of medicines in Russia. The analysis of the major causes of failure when performing studies of bioequivalence and pharmacokinetics.